COPING STRATEGIES OF COMMUNITIES AFFECTED BY THE BOHOL EARTHQUAKE - Cutillas, Anesito L; Alburo, Rosalyn P; Alburo, Hemres M; Pascual, Pet Roey L (Journal of Agriculture and Technology Management, 2018)
This article establishes existing knowledge on natural disasters and coping strategies employed in reducing the impacts caused by the 7.2 magnitude earthquake in Bohol, Philippines. The purpose of the study was to determine useful measures in terms of service options and for disaster risks management. More particularly, it aimed at assessing coping strategies employed in reducing the disaster risk and integrating knowledge of disasters and hazards. The study was carried out in the municipalities of Maribojoc and Loon which included recording people's perceptions, knowledge and attitudes towards earthquake. It employed focus group discussions and interviews in order to capture the actual situation relating to risk and vulnerability assessments by the community. The study revealed that the respondents were having a little knowledge regarding the secondary impacts of the earthquake, thus their houses are not designed against such a calamity. The study showed that the community's coping strategies consist in mainly relying on relief goods and assistance. The study further revealed that in order to prepare themselves for incoming disasters like that of an earthquake, a low cost service strategy option was chosen by the respondents. It is thus recommended that the respective LGUs of Loon and Maribojoc set up the chosen service option in their communities to inform and educate them about the hazards and devastating impacts of an earthquake and minimize if not avoid more damages.